2011
DOI: 10.1111/j.1468-2397.2011.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Unheard voices, unmapped terrain: Care work in long‐term residential care for older people in Canada and Sweden

Abstract: This article aims to contribute to comparative welfare state research by analysing the everyday work life of long-term care facility workers in Canada and Sweden. The study's empirical base was a survey of fixed and open-ended questions; this article presents results from a subset of respondents (Care Aides and Assistant Nurses) working in facilities in three Canadian provinces (n=557) and across Sweden (n=292). The workers' experiences were linked to the broader economic and organisational contexts of residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 16 publications
1
69
0
3
Order By: Relevance
“…Care workers feel inadequate and frustrated when they cannot provide the older person with the care they consider essential and in accordance with care rationality. High levels of absenteeism, due to sickness, and difficulties in recruiting staff on a permanent or temporary basis have also been reported in the Nordic eldercare research (Dellve 2003;Trydegård 2005;Elstad and Vabø 2008;Daly and Szebehely 2011). Despite these insights there is a lack of empirical studies on the impact of the ongoing organisational changes of the welfare services.…”
Section: Care Workers and Their Working Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Care workers feel inadequate and frustrated when they cannot provide the older person with the care they consider essential and in accordance with care rationality. High levels of absenteeism, due to sickness, and difficulties in recruiting staff on a permanent or temporary basis have also been reported in the Nordic eldercare research (Dellve 2003;Trydegård 2005;Elstad and Vabø 2008;Daly and Szebehely 2011). Despite these insights there is a lack of empirical studies on the impact of the ongoing organisational changes of the welfare services.…”
Section: Care Workers and Their Working Conditionsmentioning
confidence: 99%
“…In numerous studies and theoretical analyses researchers have demonstrated that caring and care work-paid as well as unpaid-are characterized by a combination of manual, intellectual and emotional work (Daly and Szebehely 2011). Care work includes both manual household tasks like cleaning, laundry and cooking as well as personal care such as bathing and dressing.…”
Section: Care Workers and Their Working Conditionsmentioning
confidence: 99%
“…What happens when unscheduled working hours are introduced in elderly care services in order to convert part-time into full-time employment jobs? Against the backdrop of the shortage of research on ongoing organizational changes on care workers´ working conditions (Daly & Szebehely, 2012;Jonsson, 2011;Trygdegård, 2012) as well as on how different forms of work hour schedules and shifts affect employees (Åkerstedt et al, 2012;Kecklund et al, 2010), it is urgent to investigate how these new work conditions are perceived by employees and not least how they affect the provision of care for the elderly. Knowledge of how care workers experience the changes made and their effect on the content of care work is missing.…”
Section: Full-time Employment In Elderly Care Through Unscheduled Wormentioning
confidence: 99%
“…Lower income also means lower reimbursement rates for parental and sick leave, unemployment benefits, and lower pension payment. The biggest part-time employer is the care service sector (Jönsson & Hartman, 2008), where part-time is more common than full-time employment for the two biggest occupational groups in Sweden, namely nursing assistants and care assistants (i.e., care workers) (Daly & Szebehely, 2012;Werkelin Ahlin & Vinge, 2013), of whom 93% are women (SCB, 2014b). The most common reason for working part-time is that full-time employment is not offered (SCB, 2014a), which is more than twice as common regarding women (162,000) than men (79,000) (SCB, 2014b).…”
mentioning
confidence: 99%
“…This includes registered nurses (RNs), licensed practical nurses (LPNs) and personal support workers (PSWs). There is a requirement that at least one RN be on duty at all times to provide medical care, but there is no minimum staffing level and most of the direct body care is provided by PSWs (Daly & Szebehely, 2012;Estabrooks et al, 2015). While the complexity of residents' needs have increased, funding and staffing have not kept pace (Armstrong & Daly, 2004;Bowers, Esmond, & Jacobson, 2000;Ontario Council of Hospital Unions, 2014).…”
Section: Ltc In Ontario and The Use Of Private Companionsmentioning
confidence: 99%